PENGARUH PENDAPATAN PERKAPITA DAN TINGKAT SUKU BUNGA TERHADAP PERMINTAAN POLIS ASURANSI JIWA - Fitroh Yuni Prakatiwi (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2014)
The research aimed to (1) find out how much the influence of per capita income and interest level to life-insurance policy demand of AJB Bumiputera 1912 Dieng Branch of Malang, (2) find out variables with dominant influence to the request of life-insurance for AJB Bumiputer 1912 Dieng Branch of Malang, (3) as landscape or information for similar research related with life-insurance in the near future. Data taken by the writer was secondary data where the data found from AJB Bumiputera 1912 Dieng Branch of Malang and BPS Malang. While data used for multiple analysis and hypothesis test using T test and F test. Regression analysis result showed that interest level (x1) influenced 4.022152 while per capita income (x2) influenced 11.11860 and determination coefficient 0.930052. So the strongest variable to the life-insurance request was per capita income (x2) with hypothesis test count 11.11860 where the coefficient determination was 0.930052.